Inhibition of HOX/PBX dimer formation leads to necroptosis in acute myeloid leukemia cells - Alharbi, Raed A.; Pandha, Hardev S.; Simpson, Guy R.; Pettengell, Ruth; Poterlowicz, Krzysztof; Thompson, Alexander; Harrington, Kevin; El-Tanani, Mohamed; Morgan, Richard (Impact Journals, 2017)
The HOX genes encode a family of transcription factors that have key roles in both development and malignancy. Disrupting the interaction between HOX proteins and their binding partner, PBX, has been shown to cause apoptotic cell death in a range of solid tumors. However, despite HOX proteins playing a particularly significant role in acute myeloid leukemia (AML), the relationship between HOX gene expression and patient survival has not been evaluated (with the exception of HOXA9), and the mechanism by which HOX/PBX inhibition induces cell death in this malignancy is not well understood. In this study, we show that the expression of HOXA5, HOXB2, HOXB4, HOXB9, and HOXC9, but not HOXA9, in primary AML samples is significantly related to survival. Furthermore, the previously described inhibitor of HOX/PBX dimerization, HXR9, is cytotoxic to both AML-derived cell lines and primary AML cells from patients. The mechanism of cell death is not dependent on apoptosis but instead involves a regulated form of necrosis referred to as necroptosis. HXR9-induced necroptosis is enhanced by inhibitors of protein kinase C (PKC) signaling, and HXR9 combined with the PKC inhibitor Ro31 causes a significantly greater reduction in tumor growth compared to either reagent alone.